Brokerage dalam Politik Lokal: Karakteristik Patron-Klien Wilayah Abangan pada Pilkada Kabupaten Blitar Tahun 2020 - Dyah Ayu Widyarini (CV. Era Digital Nusantara, 2022)
Abstract: This article analyzes the patterns of relations held by brokers in areas that have an abangan culture. The broker in this study is botoh who acts as an intermediary between candidates and prospective voters in the 2020 Blitar Regency Pilkada (Regional Elections). The theory used is the contemporary patron-client theory proposed by James C. Scott, which aims to explore the patron-client characteristics possessed by botoh in Blitar Regency. Purpose: This study aims to understand the characteristics of patron-client relationship patterns found in the abangan region of Blitar Regency. In the Pilkada held in 2020, there is a relationship formed between candidate pairs, botoh, and clients. The relationship was formed because of the opportunities for benefits obtained by each party. Design/Methodology/Approach Descriptive qualitative research methods and in-depth interviews for information gathering can explain the patron-client characteristics of botoh. Findings: This study shows that botoh in abangan areas have seven characteristics, those are (1) short-term relationship span with candidates but long-term relationship span with their subordinates, (2) profit-based relationship pattern with both candidates and subordinates, (3) specialized influence on patrons and clients who have interests, (4) has a modern managed resource base, (5) minimal control over local resources, (6) botoh and his men are one of the community groups in Blitar Regency, (7) botoh has a dense relationship with patrons and clients who have similar characteristics. Originality/Value: This research focuses on understanding the characteristics of patron-client relationship patterns found in the abangan region of Blitar Regency.